Red in Tooth and Claw No More: Animal Rights and the Permissibility to Redesign Nature. (1st April 2022) - Kianpour, Connor K.; Paez, Eze
Abstract : Most non-human animals live in the wild and it is probable that suffering predominates in their lives due to natural events. Humans may at some point be able to engage in paradise engineering, or the modification of nature and animal organisms themselves, to improve the well-being of wild animals. We may, in other words, make nature 'red in tooth and claw' no more. We argue that this creates a tension between environmental ethics and animal ethics which is likely insurmountable. First, we argue that concern for the environment can be compatible with helping individual wild animals but should see redesigning nature as morally impermissible. Second, we argue that if we are concerned with animal well-being, we may reject that we have a duty to help wild animals even to the point of redesigning nature, but we must nevertheless concede that it is permissible to do so under certain circumstances. We show how this permissibility can be derived from three animal rights views: Tom Regan's, a novel account inspired by Thomas Pogge and a libertarian approach to animal rights.